The association between students' confidence and ability to modulate spinal manipulation force–time characteristics of specific target forces: a cross-sectional study. - Nim, Casper; Smith, Nicole; Starmer, David; Wang, Simon; Choi, Grand; Alayed, Akram; AlShareef, Jomana; Gnjatic, Angela; Sloan, Keegan; Wong, Kitlyn; Funabashi, Martha (Chiropractic & Manual Therapies, 2024)
Background: Spinal manipulative therapy (SMT) is a guideline-recommended care for musculoskeletal pain taught in various undergraduate programs. Visual feedback through force-sensing tables can improve modulation of SMT force–time characteristics and, potentially, students' confidence, both factors important for clinical competence and patient outcomes. However, it is unclear if a link exists between students' confidence and ability in SMT force–time modulation. We aim to investigate this relationship and whether it was moderated by experience. Methods: This cross-sectional study recruited first- to third-year Canadian Memorial Chiropractic College students. Participants provided information about their confidence in performing SMT using different impulse forces of 200N, 400N, and 800N with a pre-established pre-load and a time-to-peak force < 150ms. SMT impulse forces of 200N, 400N, and 800N were targeted on a Human Analogue Mannequin positioned prone on a force-sensing table. We described the confidence levels and SMT force–time characteristics and assessed their association using linear mixed models. We re-ran the models interacting with SMT experience. The order of the three SMT impulse forces was randomly performed. Participants and outcome assessors were blinded to force–time characteristics recordings. Results: One-hundred-and-forty-nine participants provided usable data. Participants were confident in delivering 200N and 400N impulse forces. However, confidence decreased for 800N forces. Accordingly, participants performed impulse forces close to the 200N and 400N but had difficulty accurately modulating to 800N forces. A positive association was found between confidence and the ability to modulate their force–time characteristics, especially keeping the same pre-load force, keeping the time to peak force < 150ms, and providing the 800N impulse force. This association was not moderated by experience. Conclusions: Students were more confident in their abilities to perform lower SMT forces but lacked confidence in their abilities to perform higher (800N) forces. This aligned with their skills, as many struggled to apply 800N force. However, students who had higher confidence levels generally performed better overall. There was substantial variability in SMT force–time characteristics, which may have implications for adverse events and patient satisfaction. Some of this variability could be attributed to students' confidence. Thus, further investigations are necessary in undergraduate settings to implement and optimize these findings. Registration: https://osf.io/6f7d5